Coronal pulp biomarker: A lesser known age estimation modality - Smrithi D Veera; Jayanthi Kannabiran; Nagarathna Suratkal; Dayananda Bagur Chidananada; Kumar Raghav Gujjar; Suresh Goli (Wolters Kluwer Medknow Publications, 2014)
Introduction: The evolving state of art digital technology currently available is opening new avenues in forensic odontology for age estimation methods which are subject to debate in terms of accuracy and precision. A study was carried to analyze efficacy and practical application for age estimation using digital panoramic radiographs on South Indian population. Aims and Objectives: 1. To study reduction of coronal pulp chamber using Tooth Coronal Index (TCI) on panoramic radiographs and correlate with chronologic age. 2. To establish accuracy of digital panoramic radiographs as a simple, non-invasive tool. Materials and Methods: The study illustrates the potential value of a little known aging method. The study groups comprised a total of 100 subjects of both sexes in age range of 20 and 60 years each who were subjected to panoramic radiography. A panoramic radiographic examination using digital panoramic machine was conducted on selected individuals. The TCI was calibrated using AGFA computer software for accuracy and precision. The values obtained were subjected to regression analysis, results calculated and correlated with chronologic age. In the present study a population of known age was studied and subjected to digital panoramic radiographic examination. The correlation between reduction of coronal pulp cavity and chronological age was examined. TCI was computed for each tooth and regressed on real age. Statistical Analysis Used: Pearson correlation co-efficient was used to find the significance of relationship between age and TCI. Regression analysis has been used for predicting age using TCI for premolar and molar. Inaccuracy and bias have been determined to assess the precision of prediction equations. Results and Conclusion: Prediction potential of TCI comes down for ages above 50 years and is comfortably good below 50 years without much difference between premolars and molars. This study demonstrates the potential value of TCI for age estimation.